« Feeling at Home » in the Museum - Marie-Josée Blanchard; David Howes (Anthropologie et Sociétés, 2015)
How can the sensorial and symbolic complexity of a culture be presented within a museum space that already has its own sensorial regime, one that is often limited to the sense of vision ? This article explores the role of sense perception in museum space through an analysis of the new permanent exhibition This Is Our Story : First Nations and Inuit in the 21st Century at the Musée de la civilisation in Québec City. Through a comparison of autochthonous sensory realities and the presentation that is made of them in the case of three key examples from the exhibition, we show how sensory display strategies have the potential to enable visitors to immerse themselves in autochthonous environments and to make better sense of their symbolic and cultural importance. However, despite all the effort spent consulting source communities in the preparatory stage of the exhibition, and designing the exhibition itself, the eventual way in which the objects were displayed did not correspond to the ideas that the communities wanted to see expressed by means of the objects. The communities had clearly expressed the wish to « feel at home » in the museum space, but never succeeded at identifying fully with it given the gap between the museum sensorium and the autochthonous sensoria. Comment présenter la complexité sensorielle et symbolique d’une culture à l’intérieur d’un espace muséal qui possède lui-même un régime sensoriel souvent limité à la perception visuelle ? Cet article cherche à comprendre le rôle des perceptions sensorielles dans l’espace muséal à travers l’analyse de la nouvelle exposition permanente C’est notre histoire. Premières Nations et Inuit du XXIe siècle du Musée de la civilisation à Québec. En comparant les réalités sensorielles autochtones en Amérique du Nord et la présentation qui en est faite au Musée à travers trois exemples, nous démontrerons comment les stratégies de présentation d’objets faisant appel aux sens permettent au visiteur de se plonger dans les environnements autochtones et d’en saisir ...